The development of a prototype of polluted gas reducing instrument used for gasoline vehicle - Potivejkul, S.; Kitwattana, K.; Udomdat, P.; Kinnares, V. (My University, 2015)
This paper presents the development of a prototype of polluted gas reducing instrument which used for a gasoline vehicle. Effect of the electric field between electrodes in the instrument to capability in polluted gas reduction has been studied. In experiments, the electric field of 0-25 kV/cm 20kHz was varied. The revolution speed of engine was set to be 700 rpm. Electrode is wire-plan with 2 layer insulated acrylic plastic and air are 3 mm both of them. It is not necessary to use another power supply from outside the vehicle, since the battery used in the vehicle is used as a power supply of the instrument. The prototype can operate very well. The results showed that using only vehicle battery can provide energy to the electrodes to generate an electric field for reducing emission gases. Actually, it can reduce carbon monoxide, carbon dioxide and hydrocarbons by 36.3%, 21.6% and 9.1% respectively.
Keywords: electric field; emission gases; gasoline engine